2020
DOI: 10.29328/journal.cjog.1001045
|View full text |Cite
|
Sign up to set email alerts
|

Timely initiation of breastfeeding and associated factors among mothers who have infants less than six months of age in Gunchire Town, Southern Ethiopia 2019

Abstract: Background: Timely starting of breastfeeding is defi ned as the starting of breastfeeding within one hour after childbirth. Globally mothers who practiced breastfeeding within one hour were less than half in percent. In least developed countries like Eastern and Southern Africa including Ethiopia infant breastfeeding practice within one hour were low. The aim of this study was to assess timely initiation of breastfeeding and associated factors among mothers who have an infant less than six months of age in Gun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
3
9
1
Order By: Relevance
“…The study at hand revealed that women who delivered at a health facility were more likely to initiate breast feeding within the first 1 hour of birth than their counterparts. This finding is in line with studies conducted in South Ethiopia, 41 Northwest Ethiopia, 26 38 Economic Community of West African States, 45 sub-Saharan Africa, 33 Peru 46 and Romania. 47 As it is stated in literature, initiation of breast feeding within the first hour of birth is an integral part of the safe delivery procedure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study at hand revealed that women who delivered at a health facility were more likely to initiate breast feeding within the first 1 hour of birth than their counterparts. This finding is in line with studies conducted in South Ethiopia, 41 Northwest Ethiopia, 26 38 Economic Community of West African States, 45 sub-Saharan Africa, 33 Peru 46 and Romania. 47 As it is stated in literature, initiation of breast feeding within the first hour of birth is an integral part of the safe delivery procedure.…”
Section: Discussionsupporting
confidence: 92%
“…The finding was consistent with other study findings done in different parts of Ethiopia13 37 38 and Malawi 39. Conversely, the prevalence was lower than the studies conducted in South Ethiopia,12 40–42 North Ethiopia43 and Tanzania 44. These discrepancies could be due to the variation of the study period, access and utilisation of health service and sociocultural conditions among the respondents.…”
Section: Discussionsupporting
confidence: 90%
“…Several factors related to the mother and the baby affect the initiation of breastfeeding. Mode of delivery is one of these factors (11)(12)(13)(14)(15)(16)(17)(18)(19). When a mother has a cesarean section, she becomes a surgical patient, with all the dangers and complications it entails.…”
Section: Introductionmentioning
confidence: 99%
“…27 Skin-to-skin contact between mothers and their newborns immediately after delivery facilitates the EIBF within the first hour of delivery. [29][30][31][32][33][34][35]…”
Section: Discussionmentioning
confidence: 99%
“…26 Studies support that immediate skin-to-skin contact of mother-baby dyads positively affects the EIBF. [29][30][31][32][33][34][35] We studied the EIBF among mother-baby dyads with immediate skin-to-skin contact. There are lists of studies regarding the EIBF in Ethiopia.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%